2012
DOI: 10.1123/jpah.9.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Questionnaire to Assess Sedentary and Active Behaviors in the Southern Community Cohort Study

Abstract: Background-Low physical activity (PA) is linked to cancer and other diseases prevalent in racial/ethnic minorities and low-income populations. This study evaluated the PA questionnaire (PAQ) used in the Southern Cohort Community Study, a prospective investigation of health disparities between African-American and white adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 43 publications
0
31
2
Order By: Relevance
“…Because of the prospective study design, misclassification is expected to be non-differential and likely will attenuate study results. Additionally, validation studies found physical activity and sedentary behavior questionnaires used in the SCCS to correlate with relevant criterion measures, 40 and food frequency questionnaire estimates significantly correlate with biochemical indicators of micronutrient levels. 15 Both validation studies found the performance of the SCCS questionnaire in regard to physical activity, sedentary behavior, and diet to be consistent across racial subgroups.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the prospective study design, misclassification is expected to be non-differential and likely will attenuate study results. Additionally, validation studies found physical activity and sedentary behavior questionnaires used in the SCCS to correlate with relevant criterion measures, 40 and food frequency questionnaire estimates significantly correlate with biochemical indicators of micronutrient levels. 15 Both validation studies found the performance of the SCCS questionnaire in regard to physical activity, sedentary behavior, and diet to be consistent across racial subgroups.…”
Section: Discussionmentioning
confidence: 97%
“…The study questionnaire (available online) (17) contained questions about demographic, medical, familial, lifestyle and other participant characteristics. It also contained a physical activity questionnaire (18) and an 89-item food frequency questionnaire (19, 20). …”
Section: Methodsmentioning
confidence: 99%
“…The SCCS PAQ was evaluated in 118 participants (87 black, 31 white) using test-retest reliability methodology and via comparisons with a physical activity monitor (accelerometer) and a last-month physical activity survey administered up to four times in each participant, and there was general consistency in the magnitude of correlations between blacks and whites in the validation study (18). …”
Section: Methodsmentioning
confidence: 99%
“…The evidence for validity and reliability was similar to that documented for other self-report PA instruments in two systematic reviews 4,8 and low-income populations. 29,30 However, our data suggest that the modified RESIDE questionnaire may not capture PA as accurately among women with a BMI ≥ 37 kg/m 2 and employed women. Modifications that may improve the validity of the questionnaire include additional items to capture occupational and light intensity PA, specifically walking at work, and contextual cues to aid respondents in recalling short-duration PA bouts.…”
Section: Discussionmentioning
confidence: 66%